Reporting Incidents in the Psychiatric Intensive Care Unit: A Retrospective Study in an Italian University Hospital. Issue 8 (8th August 2022) - Mele, Federica; Buongiorno, Luigi; Montalbò, Domenico; Ferorelli, Davide; Solarino, Biagio; Zotti, Fiorenza; Carabellese, Felice Francesco; Catanesi, Roberto; Bertolino, Alessandro; Dell'Erba, Alessandro; Mandarelli, Gabriele
Abstract: To evaluate the characteristics of the reported workplace violence in a psychiatric intensive care unit (PICU) by analyzing an electronic hospital incident reporting system (IRS). One hundred thirty reports were retrieved from January 2017 to June 2020, referring to assaults committed by patients (71% males) with an average age of 29.8 years (SD, 14.9). The most frequent psychiatric diagnosis was a neurodevelopmental disorder (33%). Physical aggression (84%) was more frequent than the other types of aggression. Nurses and unlicensed assistive personnel were the most frequent victims (65%). Aggressions were more frequent on Friday (18%) and between 4 p.m. and 8 p.m. (35%). A total of 64.9% of the incidents happened in the first 5 days of hospitalization. A significant association between physical aggression and diagnosis of neurodevelopmental disorder emerged. IRS could be helpful to identify high-risk patient groups and develop clinical strategies to reduce adverse events in clinical practice.